Application of Project Based Learning Model to Improve Critical Thinking Skills of Students SMA Muhammadiyah 1 Sragen - Purwanti, Tasya Cahya Dwi; Astuti, Rina (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2023)
The goal of education is to develop each person's potential and competence so they can become good people. This study uses the Project Based Learning (PjBL) instructional model to enhance students' critical thinking abilities. Research types Qualitative description with a one-group pretest-posttest design that is pre-experimental in nature. 29 students make up the sample in this study. Tests and documentation are the tools used to obtain research data. The average posttest scores on each measure of the capacity to think critically have improved, according to the data. It is clear from the t-test findings that there is a significant difference between the pretest and posttest scores because the result was 0.000 ˂ 0.05. The use of the Project Based Learning (PjBL) learning model in class X SMA Muhammadiyah 1 Sragen resulted in a boost in students' critical thinking abilities.